(untitled) (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
The development of financial technology, or fintech, has changed the global financial industry landscape, including in Indonesia, by offering innovations that facilitate access to financial services for the public. However, this rapid growth raises questions about its impact on the performance of conventional banks. This study aims to explore the interaction between fintech and traditional banking and its implications for bank financial performance, which is crucial for helping conventional banks formulate effective adaptation strategies in the digital age. The method used in this study is quantitative, employing panel data regression analysis to identify the relationship between independent variables—mobile banking, internet banking, and SMS banking—and dependent variables encompassing bank financial performance ratios such as ROA, ROE, and NIM. The results indicate that mobile banking has a significant positive impact on ROA, while internet banking and SMS banking do not show the same effect. Additionally, all three types of services do not have a significant impact on ROE and NIM. These findings are expected to serve as an evaluation for conventional banks to innovate appropriately in competing in the digital market, as well as a consideration for policymakers in formulating regulations and support for banks seeking to adopt fintech.